Parents' Responsibilities towards Children After Divorce - Islamiyah, Nurul; Nurlia Mamonto, Andi Annisa; Stoffel, Mukti (Faculty of Law, Universitas Muslim Indonesia, 2025)
The fact of people's responsibility towards children after divorce in Jayapura City, fathers often ignore the obligation to provide for children, so that mothers as the holder of custody bear all the needs of the child. The father's reasons include economic problems, new marriage, psychological, and the assumption that the mother is capable. And legal analysis shows that the rights of children after divorce are regulated in Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law, which requires parents, especially fathers, to bear the costs of children until adulthood. However, many divorced parents do not fulfill these responsibilities, violating Article 14 of the Child Protection Law which regulates children's rights and parental responsibilities after divorce. Children's rights after divorce are regulated by law, but many divorced parents do not fulfill their responsibilities, violating child protection provisions.